Effects of biochar on berseem clover (Trifolium alexandrinum, L.) growth and heavy metal (Cd, Cr, Cu, Ni, Pb, and Zn) accumulation. (January 2022) - Pescatore, Antonio; Grassi, Chiara; Rizzo, Andrea Maria; Orlandini, Simone; Napoli, Marco
Abstract: Urban soil pollution by heavy metals (HMs) is a pressing problem in the development of urban agriculture (UA). In this context, the use of amendments, such as biochar, and phytoremediation are considered potentially cost-effective alternatives to conventional methods, and can be also combined to improve the remediation of soils from HMs. A pot experiment was performed to investigate the combined effect of berseem clover ( Trifolium alexandrinum, L.) and biochar amendment in remediating a sandy soil collected near a shooting range area co-contaminated with Cd, Cr, Cu, Ni, Pb, and Zn. The biochar, obtained from a wood-chip gasifier fed with a mix of Douglas ( Pseudotsuga menziesii, Mirb.) and Black Pine ( Pinus nigra, J.F.Arnold) wood, was applied at two rates (0.8% and 1.6%, w/w). Eighteen weeks after sowing, all plants were harvested. The roots and aboveground tissues of the crops were separately collected and analyzed. The tested biochar effectively adsorbed the HMs (Cd, Cr, Cu, Ni, Pb, and Zn) from the soil. Biochar increased DW production of aboveground and root tissues. Moreover, biochar significantly reduced the concentration of Cr, Cu, Ni, and Pb in the aboveground tissues of berseem clover, although a significant reduction was not detected for Cd and Zn. Results indicated that berseem clover was a Cr, Ni and Pb excluder. However, this species can be considered suitable for Cu phytoextraction and Cd and Zn phytostabilization of slightly polluted urban soil. Only the Cu levels in the aerial biomass were below the acceptable limit for use as fodder. Highlights: The tested biochar effectively adsorbed Cd, Cr, Cu, Ni, Pb, and Zn from soil. Dry weight of berseem clover was found increased in biochar amended soil. HMs in aboveground tissues of berseem clover decreased in biochar amended soil. Berseem clover was suitable for Cu phytoextraction while Cd and Zn phytostabilization.